Feasibility, acceptability and appropriateness of laparoscopic versus abdominal hysterectomy for women and healthcare professionals: the LAVA trial qualitative process evaluation - Matthews, Lynsay; Clark, T Justin; Bevan, Sheriden; Middleton, Lee; Antoun, Lina; Smith, Paul; Saridogan, Ertan; Woolley, Rebecca; Morgan, Monique; Jones, Laura L (Health technology assessment (Winchester, England), 2025)
Laparoscopic hysterectomies performed for benign gynaecological conditions are increasing. However, there is a lack of up-to-date evidence on their surgical outcomes when compared with abdominal hysterectomy. The LAparoscopic Versus Abdominal hysterectomy trial aimed to address this gap. A qualitative process evaluation was embedded within the pilot phase of the LAparoscopic Versus Abdominal hysterectomy trial. To explore the feasibility, acceptability and appropriateness of LAparoscopic Versus Abdominal hysterectomy for women and healthcare professionals. A qualitative process evaluation using semistructured interviews informed by the Medical Research Council/National Institute for Health and Care Research updated Framework for Developing and Evaluating Complex Interventions. Interviews were thematically analysed to inform the development of a LAparoscopic Versus Abdominal hysterectomy trial programme theory (used to demonstrate how an intervention is expected to lead to its effects, under what conditions and for which stakeholders). Eligible women and healthcare professionals (gynaecologists, research nurses and research midwives) from participating clinical sites in National Health Service England. Insight on the feasibility,acceptability and appropriateness of LAparoscopic Versus Abdominal hysterectomy related to the: (1) environment, (2) patient and (3) the healthcare professionals. Eleven women and 7 healthcare professionals (6 research nurses and 1 consultant gynaecologist) were interviewed. Four themes were interpreted. Theme 1 identified for LAparoscopic Versus Abdominal hysterectomy participation. motivated women to participate, alongside the 'relief' of being offered a hysterectomy. The decision to decline participation was influenced by surgical preference and beliefs of laparoscopy having a faster recovery rate. Theme 2 highlighted , with women's preferences being influenced by their previous experiences of surgery or perceived recovery times and family/friends. All healthcare professionals demonstrated but did observe that 'younger surgeons' may prefer laparoscopic surgery based on their contemporary training. Theme 3 identified , with women and healthcare professionals reporting positively about LAparoscopic Versus Abdominal hysterectomy's feasibility, acceptability and appropriateness in terms of burden, information and understanding of the study. Theme 4 identified the for LAparoscopic Versus Abdominal hysterectomy participation. Facilitators included the key role of the research nurses and women having personal social support during their recovery. Telephone consultations may be a barrier, with face-to-face discussion being preferred by both women and healthcare professionals. These findings informed the refinement of the LAparoscopic Versus Abdominal hysterectomy programme theory, identifying the interplay of factors related to the environment, patient and healthcare professionals. The majority of insight from women was gathered from one site (72.7%), and the majority of healthcare professionals' insight was obtained from research nurses (85.7%). Only English-speaking participants were recruited into LAparoscopic Versus Abdominal hysterectomy. Overall, LAparoscopic Versus Abdominal hysterectomy was acceptable for women and healthcare professionals. The trial, however, closed early due to the negative impact of the COVID-19 pandemic and lack of healthcare professional equipoise (these findings were published previously). The qualitative process evaluation highlighted additional factors to consider for future trials, including influences on women's decision-making and the challenges of addressing patient and healthcare professional equipoise. Comparison of laparoscopic and abdominal hysterectomy outcomes still need to be explored in a large-scale randomised controlled trial. Further qualitative insight is needed from women who decline participation and from healthcare professionals who lack equipoise. This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number NIHR128991.